2021
DOI: 10.3389/fimmu.2021.799124
|View full text |Cite
|
Sign up to set email alerts
|

Increased Platelet-CD4+ T Cell Aggregates Are Correlated With HIV-1 Permissiveness and CD4+ T Cell Loss

Abstract: Chronic HIV-1 infection is associated with persistent inflammation, which contributes to disease progression. Platelet-T cell aggregates play a critical role in maintaining inflammation. However, the phenotypic characteristics and clinical significance of platelet-CD4+ T cell aggregates remain unclear in different HIV-infected populations. In this study, we quantified and characterized platelet-CD4+ T cell aggregates in the peripheral blood of treatment-naïve HIV-1-infected individuals (TNs), immunological res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…A multicenter cohort study reported that levels of inflammatory and immune activation biomarkers, including sCD163, declined following ART initiation (71). Some studies have also reported no elevated sCD163 levels in PLWH after ART (72, 73 (68). Additionally, the percentage of platelet-CD4+ T cell aggregates was positively linked with the expression of sCD14 and sCD163, which were connected to an enhanced risk of cardiovascular disease (CVD) and can function as indicators of the evolution of HIV illness (75-77).…”
Section: Soluble Cd163mentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter cohort study reported that levels of inflammatory and immune activation biomarkers, including sCD163, declined following ART initiation (71). Some studies have also reported no elevated sCD163 levels in PLWH after ART (72, 73 (68). Additionally, the percentage of platelet-CD4+ T cell aggregates was positively linked with the expression of sCD14 and sCD163, which were connected to an enhanced risk of cardiovascular disease (CVD) and can function as indicators of the evolution of HIV illness (75-77).…”
Section: Soluble Cd163mentioning
confidence: 99%
“…Xiaopeng Dai et al. found that plasma sCD163 levels were shown to be higher in INRs compared with UCs, and that ART boosted sCD163 levels in IRs ( 68 ). Additionally, the percentage of platelet-CD4+ T cell aggregates was positively linked with the expression of sCD14 and sCD163, which were connected to an enhanced risk of cardiovascular disease (CVD) and can function as indicators of the evolution of HIV illness ( 75 77 ).…”
Section: Plasma Markersmentioning
confidence: 99%
“…In HIV infection, it has been described that activated platelets binding to CD8 + and CD4 + T cells prevent proper activation and control long-term immune dysfunction. 67 However, whether these mechanisms are mediated by eATP or chronic purinergic receptor activation is not well described. Our data indicate that healthy eATP and HAD-associated eATP levels did not change the expression and distribution of key adhesion and junctional molecules, suggesting an adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelet-derived IL-33, Dkk-1, and 5-HT or CD40L induce type 2 immune response or interact with TSLP-stimulated myeloid DCs to tune the sensitization stage of allergic asthma through RANK/ RANKL signaling (128). In addition, platelet-CD4 + T-cell aggregate frequency was positively correlated with HIV-1 viral load and was related to immune activation during HIV-1 infection (129). HIV-containing platelets result in dysfunction of glycolysis-mediated energy production in CD4 + T cells.…”
Section: T Cellsmentioning
confidence: 99%